The extrusion properties of potato granules - Kooi, Eng Teong (1982)
Potato granules from different sources were found, on extrusion, to produce potato snacks of variable quality. In some instances strip formation was unsatisfactory, in other instances blistering of the snack occurred on frying. In total, about 20-25 batches of potato granules were examined and classified in relation to these two phenomena. The amylose/amylopectin ratios of these samples of potato granules were determined by the semi-micro potentiometric iodine titration technique, but it was found that there was no significant differences in the amylose/amylopectin ratio in relation to the extrusion behaviour of the granules. The determination of the amount of free starch present outside the potato granules also did not show any clear differences between the satisfactory and unsatisfactory potato granules, though the extract from the unsatisfactory potato granules tended to indicate that they contained more lipid than the satisfactory ones. The unsatisfactory potato granules yielded a higher amount of total extractable soluble starch than their satisfactory counterpart, for the same variety of potato granules. The amount of soluble starch increased on extrusion and it was also found to be related to the breaking strength of the extrudate and their blistering behaviour. A stronger strip which gave a higher amount of soluble starch possessed a greater tendency to blister. Addition of PSA additives to potato granules prior to extrusion increased the soluble starch content, but the degree of blistering was suppressed. Gel permeation chromatography experiments showed that the starches extracted from inside the potato granules consisted of mostly high molecular weight macromolecules (very similar to that of amylopectin) and a smaller quantity of low molecular weight macromolecules similar to amylose. The soluble starch extracted from the outside of potato granules also consisted of a greater amount of high molecular weight macromolecules whereas, after extrusion, a greater quantity of smaller molecular weight macromolecules was found to be present which presumably had been expressed from the granules and was assisting in forming the network, binding the potato granules together to form a coherent strip. Determination of the total phosphate and glucose-6-phosphate contents of both potato granules and extracted starches did not show any correlation between the satisfactory and unsatisfactory potato granules. The quantities of phosphate present were small (0.8%). Studies were conducted to elucidate the differences in the cell wall material between satisfactory and unsatisfactory potato granules. Results showed only minimal differences in both the amount of cell wall material and the composition of neutral sugars in the cell wall extract of different potato granule samples. Investigations of the macromolecular order in the granules were pursued along several lines. By x-ray diffraction it was found that the manufactureof potato granules by the add-back process produced changes in the molecular order of the starch component transforming the B-type x-ray pattern of native potato starch to, in the potato granules, the A-type typically found in cereal starches. The differences in molecular order of the starch component between the satisfactory and unsatisfactory potato granules were also investigated using infra-red spectroscopy and differential scanning calorimetry besides x-ray diffractometry. However, there was no simple correlation with either the crystal type or relative crystallinity of potato granules and their extrusion behaviour. Infra-red studies also did not reveal any differences in the spectra nor the absorbance values at wavelengths of 935, 855 and 760 cm-1. D.S.C. and x-ray results, followed subsequently by lipid analysis, established that the unsatisfactory behaviour of certain batches of potato granules was due to the presence of excess GMS (>0.3%), which prevented the formation of a coherent strip, whereas satisfactory granules had a normal amount of GMS (0.3%) which was not detected by either D.S.C. or x-ray techniques. The excess GMS of unsatisfactory granules when monitored as the unassociated material (by the M L peak), was found to decrease with storage time. Extrusion of satisfactory potato granules, when examined by D.S.C. was accompanied by an increase in the amylose-lipid complex (V-amylose) as indicated by the M A-L peak and this was further enhanced on the addition of PSA additives. However, the formation of the V-amylose complex was not very evident in the x-ray patterns. X-ray crystallinity studies indicated that the extrudates exhibited a lower order and it was presumed that there was less x-ray order in the V- than in the A-form. The crystallinity of potato granule samples were found to be affected by their moisture content, the highest crystallinity was achieved with samples having approximately 38% moisture. NMR experiments in conjunction with heating experiments which had been designed to ascertain the amount of bound water before and after heating the granules to 90°C, indicated that although the bound water content before heating did not show any clear differences between satisfactory and unsatisfactory samples, there was a tendency for the unsatisfactory granules to show a slight decrease in bound water after heating. Experiments using varying amounts of water revealed that the spin-spin relaxation time (T2) increased with the water content of both satisfactory and unsatisfactory granules. The increase was greater for the satisfactory granules at 65% and 55% moisture content and lower for 45% and 35% moisture content, compared to the unsatisfactory granules. A mathematical model has been constructed which assumed that blistering was the consequence of an over-strong intergranular network which had a low permeability for water vapour. The experimental physical constraints of time, temperature and water content when introduced into the model showed that the blistering phenomenon could readily be explained. It was finally concluded that unsatisfactory strip formation was a consequence of the presence of excess GMS while blistering occurred when extrusion yielded a higher intergranular polysaccharide network (as evidenced by the amount of the total soluble starch).